Ảnh hưởng của canxi đến phản ứng metan hóa CO trên hệ xúc tác NiO/Al2O3 - Huấn, Nguyễn Mạnh; Lộc, Lưu Cẩm; Dung, Nguyễn Kim (Vietnam Journal of Chemistry, 2014)
Among NiO/Al2O3sample 37.7% NiO/Al2O3catalysts has been indicated to be the most active for CO methanation. The catalyst 37.7% NiO/γ-Al2O3, promoted by CaO with contents 5- 25% have been obtained and studied. Physico-chemical characteristics of the catalysts were determined by methods of BET Adsorption, XRD, TPR and Hydrogen Pulse Titration. The activity of the obtained samples were investigated in the reaction of CO methanation at the temperatures of 180 - 220oC and mole ratios H2/CO = 25 - 100. It has been found that the optimal content of CaO for 37.7% NiO/Al2O3sample is 10.2%.  The  activity of this catalyst is higher than 37.7% NiO/Al2O3 and 7.5% NiO/TiO2samples overagely by 11 and 30.5 times, respectively. It can completely convert CO  into methane at 180oC